IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING RECOUNT TEXT BY USING SEQUENCE OF PICTURES - Rodiah, Nurul; -, Bachtiar (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
AbstractThis study deals with the improvement of the students™ achievement in writing recounttext using sequence of pictures. This study was conducted by using action research atsecond year of SMP N 1 Kualuh Selatan. The sample of this study was just one classnamely: VIII-1. The number of this class was 35 students. This study was conducted intwo cycles and every cycle consisted three meetings. To collect the data, the instrumentsof data were used, writing test (quantitative data) and diary notes, interview sheet andobservation sheet (qualitative data). In analyzing data, the mean of the students™ scorefor the first competency test was 60,9, for the second competency test was 69,3, and forthe third competency test was 80,0 and total percentage of improvement from the firstcompetency to the third competency test was 85,72%. The conclusion is that usingsequence of pictures can improve the students™ writing achievement in recount text. It issuggested that English teacher should apply sequence of pictures as one of media toimprove students™ writing achievement in recount text.Key words: Students™ achievement, Writing, Recount text, Sequence of Pictures